1993
DOI: 10.1002/ijc.2910530603
|View full text |Cite
|
Sign up to set email alerts
|

Non‐melanoma skin cancer: Ten years of cancer‐registry‐based surveillance

Abstract: The Tasmanian Cancer Registry cam'ed out population-based surveillance of non-melanoma skin cancer (NMSC) from I978 to 1987. A total of 8.65 I NMSC were recorded in 7, I60 individuals, representing an age-standardized rate of I 6 I / I00,OOO per year.Ninety-four percent of cases were based on histological diagnosis. Incidence of basal-cell carcinoma (BCC) was higher than the incidence of squamous-cell carcinoma (SCC). The incidence of NMSC was twice as high in men as in women. Incidence increased substantially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
43
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(48 citation statements)
references
References 16 publications
3
43
0
Order By: Relevance
“…In previous epidemiologic studies, the BCC:SCC ratio varied depending on the population studied, ranging from 2.8:1 in Tasmania 20 ; 6:1 to 9:1 in northern Europe 21 ; 2.8:1 for male patients and 4.5:1 for female patients in Manitoba, Canada 22 ; and up to 11:1 in the United States. 19 Interestingly, the study by Demers et al 22 demonstrated that in Manitoba, Canada, the BCC:SCC ratio was age dependent, ranging from 8.8:1 in men and 21.8:1 in women in the age group younger than 40 years, to 1.6:1 in men and 1.5:1 in women in the age group older than 89 years.…”
Section: Discussionmentioning
confidence: 85%
“…In previous epidemiologic studies, the BCC:SCC ratio varied depending on the population studied, ranging from 2.8:1 in Tasmania 20 ; 6:1 to 9:1 in northern Europe 21 ; 2.8:1 for male patients and 4.5:1 for female patients in Manitoba, Canada 22 ; and up to 11:1 in the United States. 19 Interestingly, the study by Demers et al 22 demonstrated that in Manitoba, Canada, the BCC:SCC ratio was age dependent, ranging from 8.8:1 in men and 21.8:1 in women in the age group younger than 40 years, to 1.6:1 in men and 1.5:1 in women in the age group older than 89 years.…”
Section: Discussionmentioning
confidence: 85%
“…20,21 This study found no evidence of any increase in the proportion of younger patients or in the proportion of female patients in recent years, contradicting observations made in some international studies. [5][6][7][8][9][10][11][12][13][14] Nevertheless, a greater proportion of extra-cephalic lesions was observed in recent years compared to previous years, principally among women. This finding, which has also been reported in other studies 9 , may be due to an actual change occurring recently in the profile of patients as a result of behaviors associated with greater recreational exposure to solar radiation.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] According to some studies, as well as an increase in the incidence of this form of skin cancer, changes have also occurred in the form of presentation of BCC, including an increase in the number of lesions occurring in photo-protected areas of the body and a trend towards a greater occurrence in females; however, few studies have been carried out in Brazil to evaluate these trends. [4][5][6][7][8][9][10][11][12][13][14][15][16] In addition to sun exposure, genetic susceptibility and exposure to other environmental carcinogens are factors that have been related to the etiology of these lesions. 1,2 Therefore, behavioral and biological differences between male and female patients would be expected to result in different patterns of behavior of BCC.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that approximately 5-10% of all skin cancers occur on the eyelid [1]. In addition, studies have shown that the incidence of skin cancers is rapidly increasing [2][3][4][5][6][7][8]. Therefore, understanding the epidemiology and incidence trends of malignant eyelid tumors is important both to ophthalmologists for better clinical management and to health policy planners for suitable health care planning.…”
Section: Introductionmentioning
confidence: 99%